2015
DOI: 10.1021/jp506349t
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Photoelectrochemical Performance of CuWO4 Thin Films for Solar Water Splitting by Plasmonic Nanoparticle Functionalization

Abstract: The effect of plasmonic nanoparticles (NPs) on the photoelectrochemical water splitting performance of CuWO 4 is studied here for the first time. CuWO 4 thin films were functionalized with well-defined Au NPs in two composite configurations: with the NPs (I) at the CuWO 4 −electrolyte interface and (II) at the CuWO 4 back contact. In both cases, the incident photon to current conversion efficiency of the film was increased (∼6fold and ∼1.2-fold for configurations I and II (at λ = 390 nm), respectively). Two im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 30 publications
1
75
1
Order By: Relevance
“…25,28,29 This technique have focused on fabricating NPs using spark ablation (at low frequencies) for a number of new applications (Table S1). 3,6,7,19,25,29,[33][34][35][36][37][38]31,[39][40][41][42][43][44] Note that carrier gases and electrodes determine the particle composition. 25 Although manufacturing electrodes may not be particularly green, the use of recycled metals allows the green manufacturing of NPs.…”
Section: High-yield and Continuous Synthesis Of Ultrapure Inorganic Nmentioning
confidence: 99%
See 1 more Smart Citation
“…25,28,29 This technique have focused on fabricating NPs using spark ablation (at low frequencies) for a number of new applications (Table S1). 3,6,7,19,25,29,[33][34][35][36][37][38]31,[39][40][41][42][43][44] Note that carrier gases and electrodes determine the particle composition. 25 Although manufacturing electrodes may not be particularly green, the use of recycled metals allows the green manufacturing of NPs.…”
Section: High-yield and Continuous Synthesis Of Ultrapure Inorganic Nmentioning
confidence: 99%
“…In addition, guiding the aerosol NPs to the liquid phase opens numerous possibilities to stabilize them, which, however, results in impurities and expensive/tedious washing procedures. Besides the applications shown in Table S1, nonagglomerated singlet particles have been shown to increase the conversion efficiency of solar cells and photocatalysts for water splitting, 40,41 whereas agglomerated particles have been used to nanofinish a number of antibacterial textiles with high antibacterial activity and good washing durability. 50 With respect to nanocatalysis, we found that the agglomerated NPs at surface can be reconstructed to spheres by annealing.…”
Section: High-yield and Continuous Synthesis Of Ultrapure Inorganic Nmentioning
confidence: 99%
“…It has been shown that the incident energy absorbed by plasmonic NPs can be transferred to a nearby semiconducting photoelectrode, thereby enhancing its performance . As a result, many noble metal NP/semiconductor systems have been studied to date, in particular to improve the rate of solar photoelectrochemical reactions (e.g., water splitting for hydrogen generation and phenol degradation for water purification) . In many of these studies, the improvement of the semiconductor's performance, upon plasmonic NP functionalization, has been explained by a light trapping mechanism called local electromagnetic field enhancement or light concentration.…”
Section: Figurementioning
confidence: 99%
“…This is probably because the film with two layers is a better anchored semiconductor. Valenti et al [40] reported the enhancement of the photoelectrochemical performance using a CuWO 4 film modified by Au nanoparticle as electrode; this enhancement was attributed to a combination of effects such as plasmon resonance energy transfer (PRET), hot electron injection, and light scattering. WO 3 electrodes with two layers were functionalized with metallic nanoparticles by the photoreduction method.…”
Section: Photoelectrochemical Investigationmentioning
confidence: 99%